The Implementation of Teaching Assistance Program at SMA Panca Bhakti Pontianak - Azhari Dharmawan; Aunurr rahman; Maliqul Hafis; Rahayu Meliasari (IKIP PGRI Pontianak, 2023)
AbstractThis study aimed to describe the implementation of teaching assistance program and the challenges in implementing teaching assitance program at SMA Panca Bhakti Pontianak. This study used a descriptive study. The techniques of data collection were direct communication technique and direct observation technique. The tools of data collection were observation, and interview. The subject of this research were 7th semester students of IKIP PGRI Pontianak and the students in grade 10 and 11 of SMA Panca Bhakti Pontianak.The results of the research showed that the implementation of teaching assisstance program was succesfully regarded. All of participants carried out all the activities that have been previously arranged by the lecturers who guide them in implementing this program, even though there was one aspect of activity that all of participants could not implement because of learning at school was still limited due to the pandemic. As for challenges during the program, all of participants faced various challenges such as, in management or administration of education, in making lesson plans (RPP), students' network when online learning, the passive student when learning process, and one of participant who was still stiff in teaching.